KEPEMIMPINAN DAN SUPERVISI KEPALA SEKOLAH (Dalam Lembaga Pendidikan) - Muli Prima Aldi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2019)
In order to improve the quality of education at a level of education a strong leader is needed and the implementation of good supervision. The study of school success shows that the principal is the person who determines the focus and atmosphere of the school, therefore the success of the school is a school that has a successful leader. School leaders are those who are described as people who have high expectations of staff and students,school leaders are those who know a lot about their tasks and who determine the atmosphere for their school.